Jemimah Njuki—Working with and for women and livestock - Njuki, Jemimah (International Livestock Research Institute, 2011)
Jemimah Njuki is a specialist in issues related to women and gender in agriculture. In this short film she explains her belief that farm animals could be one way for poor women to make money, feed their families better and educate their children. "Owning animal assets gives women power" says Njuki, ... and this gives women a voice ... and when women become equal partners, everyone benefits!"